2022
DOI: 10.1111/ruso.12469
|View full text |Cite
|
Sign up to set email alerts
|

The Farming Question: Intergenerational Linkages, Gender and Youth Aspirations in Rural Zambia

Abstract: With agriculture considered key to generating jobs for Africa's growing population, several studies have explored youth aspirations toward farming. While many factors explaining aspirations have been well studied, little is known about the actors' shaping aspirations. We developed a novel framework that focuses on the factors and actors shaping the formation and actual aspirations of rural youth and applied a unique “whole‐family” approach based on mixed‐methods data collection from adolescents (boys and girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…On the one hand, in its simplest form, role modeling operates through children's direct like-for-like imitation of their parents' occupations (Bussey & Bandura, 1999). There is abundant empirical evidence of direct occupational imitation in various settings ranging from agricultural occupations in Zambia (Ogunjimi et al, 2021) to engineering careers in the United States (Jacobs et al, 2017). Most existing theories and evidence emphasize that direct occupational imitation is primarily driven by innate gender identification (Polavieja & Platt, 2014) and is thus limited to homo-lineal connections between mothers (fathers) and daughters (sons) (Bussey & Bandura, 1999;McGinn et al, 2018;Simpson, 2003).…”
Section: Gender-role Modeling: Disentangling Direct Imitation From In...mentioning
confidence: 99%
“…On the one hand, in its simplest form, role modeling operates through children's direct like-for-like imitation of their parents' occupations (Bussey & Bandura, 1999). There is abundant empirical evidence of direct occupational imitation in various settings ranging from agricultural occupations in Zambia (Ogunjimi et al, 2021) to engineering careers in the United States (Jacobs et al, 2017). Most existing theories and evidence emphasize that direct occupational imitation is primarily driven by innate gender identification (Polavieja & Platt, 2014) and is thus limited to homo-lineal connections between mothers (fathers) and daughters (sons) (Bussey & Bandura, 1999;McGinn et al, 2018;Simpson, 2003).…”
Section: Gender-role Modeling: Disentangling Direct Imitation From In...mentioning
confidence: 99%
“…Even so, the aspired farming systems in both regions appeared to be capital-intensive, contrary to current realities. While Ogunjimi et al (2023) found an association between people's current farm characteristics and their aspirations, other studies (Elias et al 2018;Bloem 2021) also found a disparity between rural realities and aspirations -a concept described as an "aspiration gap" (Ray et al, 2006).…”
Section: Discussionmentioning
confidence: 92%